Improved Nutrient Management Practices to Curtail Heavy Nitrogen Use and Enhancing Productivity and Profitability of Wheat Under Indus River Plains of Pakistan-I (SAARC Journal of Agriculture, 2025)
A field experiment consisting of integrated nutrients management (INM) and farmer practices (FP) was conducted to find out their effects on wheat crop productivity as well as soil properties. Results show that improving soil fertility by application of all required nutrients in the form of INM practice not only increased soil fertility status particularly soil pH, and macronutrients like NO3-N, P and K but also enhanced soil organic matter and carbon status. Besides improving soil properties, the INM practice also enhanced crop productivity in comparison to Farmer Practice (FP), which was confined to N-based fertilizer only.SAARC J. Agric., 23(1): 16-24 (2025)